Presentation-Practice-Production (PPP): Elicitation Technique Used by the English Teacher to Teach Grammar - Oryza, Fatma; Asad, Fitriah; Soraya, Irma (FOSTER: Journal of English Language Teaching, 2022)
ABSTRACT Presentation-Practice-Production (PPP) has been a common teaching model to improve grammar understanding. A videotaped classroom found on YouTube uses the PPP model with proper elicitations that create student-centered. This study aims to investigate the number of elicitation questions in each stage of PPP and its role to stimulate learning that most benefits students. A quantitative method was used to determine the most frequently used type of elicitation question in each stage. In addition, the data of the selected transcript extracts is qualitatively analyzed using conversational analysis. The result shows that closed-ended questions are mostly used in the presentation phase. Meanwhile, open-ended questions are mostly used in the practice and production phases. It is concluded that a close-ended question fits the stage that needs high guidance from the teacher like when lecturing. Meanwhile, the open-ended question is suitable for a stage that is freer for students to practice and explore.